1997
DOI: 10.1016/s0022-5347(01)64475-6
|View full text |Cite
|
Sign up to set email alerts
|

New Onset Hypertension After Extracorporeal Shock Wave Lithotripsy: Age Related Incidence and Prediction by Intrarenal Resistive Index

Abstract: Patients older than 60 years are at risk for disturbances of renal perfusion as assessed by the resistive index, and 45% of these patients have new onset hypertension within 26 months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 27 publications
4
60
2
Order By: Relevance
“…When we evaluated VRI using Doppler ultrasound, a significant increase in VRI was seen after ESWL. These findings are in agreement with Janetschek et al [26], who found increased VRI in the treated kidneys of patients who underwent ESWL. In addition, this overexpression of renin with a subsequent increase in angiotensin promotes the release of oxygen-free radicals (OFR) via activation of the NADPH oxidase, with the resulting activation of pro-inflammatory molecules that contribute to kidney damage [27].…”
Section: Eswl Associated Injurysupporting
confidence: 93%
“…When we evaluated VRI using Doppler ultrasound, a significant increase in VRI was seen after ESWL. These findings are in agreement with Janetschek et al [26], who found increased VRI in the treated kidneys of patients who underwent ESWL. In addition, this overexpression of renin with a subsequent increase in angiotensin promotes the release of oxygen-free radicals (OFR) via activation of the NADPH oxidase, with the resulting activation of pro-inflammatory molecules that contribute to kidney damage [27].…”
Section: Eswl Associated Injurysupporting
confidence: 93%
“…Even longer term follow-up suggests that the risk for an elevated serum creatinine level is not increased with SWL compared with percutaneous nephrolithotomy or conservative management (33). Hypertension has been described as a complication of SWL in many (34,35) but not all (32,36,37) studies. A recent population-based study did not find an increased risk with developing hypertension, suggesting that this complication is not common with most stone formers who undergo SWL (38).…”
Section: Putative Mechanisms For Ckd In Stone Formersmentioning
confidence: 99%
“…Patients over the age of 60 may develop hypertension at a higher rate than the control population, which can be predicted by increased intra renal resistive indices. Close postoperative screening for hypertension in the older patients is recommended [31].…”
Section: Eswl and Hypertensionmentioning
confidence: 99%